Perfil da Produção Brasileira sobre História da Química em Periódicos e Congressos: subsídios para a formação docente e sala de aula - Castro, Flávia Pierrotti de (Universidade Federal de São Carlos, 2015)
The History and Philosophy of Science (HFS) is recognized by many authors as contextualization instrument of scientific knowledge in Science Education, as well as teacher training. The HFC can provide the teacher, subsidies to better understand the conceptual difficulties of students, enabling a better understanding of the role of science in the development of societies. The practice teacher based on the epistemological reflections creates a better educational performance, more approaching the images of science developed in the classroom with the true nature of science, making the act of teaching a constant research process. Considering this importance, this research has the main objective to define the profile of the Brazilian intellectual production on the History of Chemistry and Science through systematic review methodology (SR), to contribute to the initial and continuing teacher training. The SR consists of rigorous and systematic overview of all research related to the specific issue through the development of structured protocol with their descriptors, inclusion and exclusion criteria and the analysis of the recovered texts. For this research, we used twelve (12) descriptors in Google Scholar database, with the inclusion criteria, texts published between 1993-2013, in Portuguese (Brazil), to bring relevant discussions relating the concepts with HFS chemicals for the formation/maturation of the knowledge of teachers, so that they can improve their teaching practice, as well as texts that present didactic sequences that contextualize the chemical knowledge to the History of Chemistry and/or Science. From crossing the descriptors, it was generated a universe of 1599 texts with 92 selected for the selective reading. In analysis of the recovered texts, 63 publications are related to the epistemological discussions, with the largest production (68,3%) in the 2006-2013 period, in Química Nova and Química Nova na Escola (41,2%), most approach has the Chemical Elements content (17,46%) and historical period being further discussion the twentieth century (23,8%). For texts related to the methodological proposal, 29 publications were analyzed, with the largest production (75,9%) in the period 2011-2013, in the proceedings of conferences (62%) highlighted the XVI Encontro Nacional de Química (24,1%), the higher was the content of approach weight Laws (17.2%) and historical period being further discussion the eighteenth century (27,6%) correlating directly with the chemical content with a higher approach. The survey sought to outline the profile of the Brazilian intellectual production over the last twenty years, present in journals and conferences because studies recovered relating to HFS with chemical concepts can be extremely relevant to the formation/maturation of teachers, so that they they can improve their teaching practice and incorporate this knowledge in their teaching sequences.
Profile of Brazilian Production of History of Chemistry in Periodic and Conferences: subsidies for teacher training and classroom
Keywords: História da Química; História da Ciência; Formação de professores; Sequências didáticas; History of Chemistry; History of Science; Teacher education; Teaching sequences; OUTROS